Seven year efficacy of RTS,S/AS01 malaria vaccine in young African children - Olotu, A; Fegan, G; Juliana, W; Nyangweso, G; Leach, A; Marc, L; Kaslow, D; Njuguna, P; Kevin, M; Bejon, P (Massachusetts Medical Society, 2016)
Background The RTS,S/AS01 malaria vaccine candidate is being evaluated for implementation. Methods We conducted 7 years follow-up of children who were randomized at age 5 to 17 months to receive three doses of either the RTS,S/AS01 vaccine or control vaccine (rabies). The endpoint was clinical malaria (temperature ≥37.5°C and infection with Plasmodium falciparum of ≥2500 parasites per µl). Each child’s malaria exposure was estimated using the prevalence of malaria among residents within a 2km radius of their homestead. Vaccine efficacy was defined as 1 minus the hazard ratio (HR) or incidence rate ratios (IRR) of the RTS,S/AS01 vaccinated versus rabies vaccinated groups. Results We identified 1002 clinical malaria episodes among 223 children randomized to RTS,S/AS01 and 992 clinical malaria episodes among 224 children randomized to control vaccination over seven years follow-up. Intention-to-treat vaccine efficacy (VE) was 4.4% (95%CI: -17 to 21.9, p value=0.67) and per-protocol VE was 7.0% (95%CI -14.5 to 24.6%, p=0.5) by negative binomial regression. VE waned over time (p=0.006 for the interaction between vaccination and time), including negative efficacy during the fifth year among children at higher malaria parasite exposure (-43.5%, 95%CI: -100.3 to -2.8, p value=0.033 by intention-to-treat and -56.8%, 95%CI -118.7 to -12.3, p=0.008 per-protocol). Conclusion A 3-dose vaccination with RTS,S/AS01 is initially protective against clinical malaria, but this is offset by rebound in later years in areas with higher malaria parasite exposure. Further data are needed on longer-term outcomes following four-dose vaccinations.